RADICAL CORRECTION OF COMBINED CONGENITAL HEART DISEASE IN PATIENT WITH EXTRAHEPATIC PORTAL HYPERTENSION - A.S. Ivanov; O.M. Tsirulnikova; S.V. Glamazda; A.V. Lebedeva; N.N. Abramova; V.V. Kuzmin; E.K. Galnykina (Вестник трансплантологии и искусственных органов, 2014)
Aim. To present rare clinical observation of successful surgical treatment of the patient with double-chamber right ventricle in combination with ventricular septal defect, subaortic fi brosis and muscular stenosis, insufficiency of the aortic valve and extrahepatic portal hypertension.Description. Patient F., 15 years old, was diagnosed with Congenital Heart Disease – double-chambered right ventricle, ventricular septal defect. Fibromuscular subaortic stenosis. Aortic valve insuffi ciency II. Circulatory failure II A., functional class III. Extrahepatic portal hypertension. Splenomegaly. Thrombocytopenia. The state after the imposition of splenorenal anastomosis in September 1998 and the imposition of mesocaval H-shaped anastomosis in 1998. Non-functioning anastomoses. Patient indicated for surgical correction of CHD, however, given the low level of platelets, expressed splenomegaly, leucopenia, the patient was referred for a preliminary treatment to Rogachev’s Pediatric Hematology, Oncology and Immunology Center. The treatment (stimulating thrombopoiesis using romiplostim) gave no signifi cant effect. Platelet count reached 70–90 Å~ 109. Seeing of frequent bleeding from esophageal varices, the patient underwent varix sclerosis. At the time of hospitalization – no esophageal varices. The patient appealed to V.I. Shumakov Federal Research Center of Transplantology and Artifi cial Organs where he was recommended for surgical treatment.Result. The patient performed surgery: radical correction of CHD: resection of the stenosis of the outfl ow tract of the right ventricle, subaortic stenosis resection, closure of ventricular septal defect, AV plasty under cardiopulmonary bypass. The early postoperative period was uneventful. Leukopenia was observed to 1,2 Å~ 109, thrombocytopenia 70–90 Å~ 109. Despite the low level of platelets bleeding in pre-and postoperative period was not registered. Antibiotic therapy with tienam. Good postoperative results were obtained. Liver function was not affected.Conclusion. Presented clinical case demonstrates the possibility of surgical intervention of combined heart disease with cardiopulmonary bypass in patient with extrahepatic portal hypertension.